Potential flue gas desulfurization gypsum utilization in agriculture: A comprehensive review. (February 2018) - Wang, Jinman; Yang, Peiling
Abstract: Over the past few decades, there has been wide interest in developing strategies for the utilization of flue gas desulfurization gypsum (FGDG), a by-product of scrubbing sulfur from combustion gases in coal-fired power generation plants. FGDG has applications in agriculture due to its function in the remediation of soil quality and crop growth. It is often economical to use FGDG as a soil amendment; however, compared to other industries, the utilization of FGDG in agriculture is very limited. A comprehensive review of numerous studies in the last few decades was conducted in this paper, which systematically covered the importance, scope, function, effect and risk regarding the utilization of FGDG in agriculture. As a remediation material, FGDG has many benefits in agriculture applications, such as improving soil physicochemical properties, controlling soil and nutrient loss, supplementing trace elements for soil and increasing crop yield. However, FGDG also contains a number of toxic trace elements. Therefore, proper attention should be paid to some important areas related to FGDG utilization, such as long-term studies of the impact of FGDG on soil health, heavy metal uptake, crop growth and quality, and continuous monitoring of the health of soil and water. The problems of salt accumulation and heavy metal toxicity due to excess application should also be addressed when FGDG is used in agriculture. Moreover, some measures and standards for the practical application of FGDG need to be proposed to promote the utilization of FGD gypsum in agriculture.